Flutter analysis and wind-tunnel experiments of a flat plate suspended by wires - Keiichi HIROAKI; Keisuke SASADA; Hiroyuki IINUMA; Masahiro WATANABE (Nihon Kikai Gakkai ronbunshu, 2023)
In the construction work, flat plates for building materials are transported by a suspension mechanism using wires in air flow. Then, a flutter could be caused to the suspended plates due to the interaction between plate motion and fluid flow. The violent vibration due to flutter loses the efficiency and safety of the operation. To improve the efficiency and safety of the operation, a detailed understanding of the flutter characteristics is crucial. In this paper, the flutter analysis and experiments of a flat plate suspended by wires in air flow are carried out. In the flutter analysis, the Doublet-point method based on the unsteady lifting surface theory is used to calculate the unsteady fluid force acting on the plate surface. The equation of motion of the plate suspended by wires considering restoring force due to gravity is derived based on the Lagrange equation. The flat plate is modeled as a rigid body. The flutter velocity and frequency are examined through the root locus of the characteristic equation of the system with changing the flow velocity. Moreover, wind - tunnel experiments are conducted to verify the analytical results. The influence of a suspending angle on the flutter velocity, frequency and mode are investigated in detail. Finally, the work done by the fluid force acting on the plate surface is examined.